Peer Innovation Tone and Corporate Innovation Adjustments: Evidence from China. (16th January 2023) - Liu, Zhiqiang; Rao, Pingui; Wang, Xinlu; Yue, Raymon
Abstract: Using textual information regarding innovation in the annual reports of Chinese listed firms for the period from 2007 to 2019, we examine how firms alter their innovation activities in response to the tone of peer firms' discussions of innovation in their annual reports ("innovation tone"). We find that a positive innovation tone in peer firms' annual reports results in a significant reduction in R&D investments by the focal firm, especially when such a tone pertains to the future. Our cross‐sectional analyses show that peers' innovation tone strongly affects R&D investments when the focal firm operates in a non‐high‐tech or highly competitive industry, or is readily willing to adjust its innovation strategy. Further investigation shows that the marginal benefits of a focal firm's R&D investments decline when annual peer reports adopt relatively positive innovation tones. Our results enrich the literature on the peer effects of textual information on innovation and have implications for firms' innovation strategies.